A model for evaluating organisation performance with application to a non-profit R&D organisation. (1st January 1997) - Ghosn, A.A.; AI-Jazzaf, M.I.; Nazar, A.
All organisations, regardless of their nature and type of work, may occasionally face external and/or internal constraints that could hamper their performance and may necessitate their restructuring as well. Thus, periodical assessment and analysis of the performance of the organisation or some of its units is needed. A general model to assess the performance of an organisation is presented here. The methodology used allows thorough scrutiny at the functional, organisational unit and the whole organisation levels. The results obtained using this model could provide grounds and tools for appropriate management decisions and actions to enhance the quality and effectiveness of the organisation. The model was successfully applied to an R&D organisation. It was concluded based on this application that it could as well be applied to other organisations if the assessment criteria are properly selected.